Analysis of the Factors Causing the Low Students' Motivation in Class IV SD Negeri 03 Nyangkom Academic Year 2020/2021 - Dwi Cahyadi Wibowo (Britain International for Academic Research (BIAR-Publisher), 2021)
The purpose of this study is to find out the factors that cause low motivation of students in grade IV sd Negeri 03 Nyangkom in the 2020/2021 school year. This research method is a skin research method with a descriptive form of research. data collection techniques using observation, indirect communication, direct communication, and documentation. Data collection tools using observation sheets, questionnaires, interview sheets, and documentation. Based on the analysis of data on the application of learning motivation in grade IV has been carried out well the application of (1) praise, (2) gift giving, (3) Ego-involvement, (4) giving the replay intended here is training or giving homework, and (5) punishment, Although the criteria of motivation to study at SD Negeri 03 nyangkom are still in the category of less that is an average of 38% and percentage of 11%.The factors behind the low motivation of learning students in grade IV SD Negeri 03 Nyangkom are (1) students lack internal motivation in themselves students prefer to play and watch television rather than study at home and (2) external factors that affect the low motivation of learning that teachers provide less variety of teaching, a less clean classroom atmosphere, and parents who are less instrumental in motivating students. As well as the dominant factor behind the low motivation of learning is the internal factor that is in (1) many students who prefer to play rather than learn and on indicators (2) lack of hope and future goals.